Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan IPA Materi Siklus Air Dengan Menggunakan Model Pembelajaran Program Di Kelas V SDN 5 Guntung Manggis - Nur Sofa; Muhammad Saleh (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low student learning activity which has an impact on student learning outcomes in learning Water Cycle Science material. The purpose of this study is to analyze teacher activities, analyze student activities, and analyze student learning outcomes. This study used a qualitative research approach with a type of classroom action research conducted in 4 meetings. The subjects of this study were grade V students of SDN 5 Guntung Manggis, the number of students was 28 students consisting of 10 male students and 18 female students. The types of data in this study are qualitative data and quantitative data. Qualitative data are obtained through observation of teacher and student activities. In addition, quantitative data is obtained through student learning outcomes. Then the results of the research obtained explained that teacher activities at meeting IV obtained "very good" criteria. Student activity at the IV meeting has reached 100% with the criterion of "very active". The classical completeness of student learning outcomes at Meeting IV has also received 100%. Furthermore, the conclusion reached in this study is that applying the PROGRAM model which is a combination of PBL, NHT, and Make a Match models can improve student activity and learning outcomes for students.